The effect of a mystery shopper scheme on prescribing behavior in primary care: Results from a field experiment - Roland Cheo; Ge Ge; Geir Godager; Rugang Liu; Jian Wang; Qiqi Wang (Health Economics Review, 2020)
Background: Health care systems in many countries are characterized by limited availability of provider performance data that can be used to design and implement welfare improving reforms in the health sector. We question whether a simple mystery shopper scheme can be an effective measure to improve primary care quality in such settings. Methods: Using a randomized treatment-control design, we conducted a field experiment in primary care clinics in a Chinese city. We investigate whether informing physicians of a forthcoming mystery shopper audit influences their prescribing behavior. The intervention effects are estimated using conditional fixed-effects logistic regression. The estimated coefficients are interpreted as marginal utilities in a choice model. Results: Our findings suggest that the mystery shopper intervention reduced the probability of prescribing overall. Moreover, the intervention had heterogeneous effects on different types of drugs. Conclusions: This study provides new evidence suggesting that announced performance auditing of primary care providers could directly affect physician behavior even when it is not combined with pay-for-performance, or measures such as reminders, feedback or educational interventions.
Keywords: C93; I11; I18; L15; M14; 330; Field experiment; Primary care; Prescription; Information and product quality; Social responsibility